2018
DOI: 10.1101/475913
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TCR and inflammatory signals tune human MAIT cells to exert specific tissue repair and effector functions

Abstract: MAIT cells are an abundant T-cell population enriched in peripheral tissues such as the liver. They are activated both through TCR-dependent andindependent mechanisms. However, the different specific functional responses of MAIT cells to these distinct signals remain elusive. We examined the impact of combinations of TCR-dependent and -independent signals in blood and tissue-derived human MAIT cells. TCR-independent activation of MAIT cells from blood and gut was maximised by extending the panel of cytokines t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…This response was more prominent with TCR activation compared to cytokine activation. Our finding was consistent with those of Leng et al, who demonstrated a similar enrichment of genes involved in tissue repair functions in TCR and TCR+cytokine but not cytokine triggered peripheral human MAIT cells (Leng et al, 2018), and Hinks et al, who reported enrichment of the tissue repair pathway in 5-OP-RU-stimulated human MAIT cells and MAIT cells from mice acutely infected with L. longbeachae (Hinks et al, 2018); this confirms that the tissue repair function is a unique signature of TCR activated MAIT cells. Therefore, it is now becoming clear that MAIT cells are not just inflammatory and cytolytic T cells but are also helper cells involved in tissue repair and maintaining homeostasis at the mucosal barrier and in the liver.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This response was more prominent with TCR activation compared to cytokine activation. Our finding was consistent with those of Leng et al, who demonstrated a similar enrichment of genes involved in tissue repair functions in TCR and TCR+cytokine but not cytokine triggered peripheral human MAIT cells (Leng et al, 2018), and Hinks et al, who reported enrichment of the tissue repair pathway in 5-OP-RU-stimulated human MAIT cells and MAIT cells from mice acutely infected with L. longbeachae (Hinks et al, 2018); this confirms that the tissue repair function is a unique signature of TCR activated MAIT cells. Therefore, it is now becoming clear that MAIT cells are not just inflammatory and cytolytic T cells but are also helper cells involved in tissue repair and maintaining homeostasis at the mucosal barrier and in the liver.…”
Section: Discussionsupporting
confidence: 93%
“…Transcriptomic signatures associated with TCR triggering could also be identified. A novel tissue repair signature proposed to be associated with TCR triggering of MAIT cells (Leng et al, 2018) was enriched in MAIT cells following E. coli or 5-A-RU stimulation but not with IL-12+IL-18 (S. Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the MAIT cell response to TCR stimulation is restricted and a co-stimulatory signal, such as that provided by T1-IFNs, is essential for full activation. While commensal bacteria may act as a source of MAIT cell TCR ligands, partially activating tissue resident MAIT cells (Leng et al, 2018; Sobkowiak et al, 2019; Tang et al, 2013), pro-inflammatory signals, including T1-IFNs, produced during infection/inflammation may synergise with the TCR signal and tune the overall MAIT cell effector response (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, MAIT cells produce pro-inflammatory cytokines such as tumour necrosis factor alpha (TNFα), interferon gamma (IFNγ), and IL-17A, as well as cytotoxic molecules (granzymes and perforin) (Billerbeck et al, 2010; Dusseaux et al, 2011; Kurioka et al, 2015; Le Bourhis et al, 2013). The exact effector functions expressed depend upon the mode of activation (Hinks et al, 2018; Lamichhane et al, 2019; Leng et al, 2018). Many in vivo studies have established an important role for MAIT cells in protection against bacterial infections (Chua et al, 2012; Georgel, Radosavljevic, Macquin, & Bahram, 2011; Meierovics, Yankelevich, & Cowley, 2013; Wang et al, 2018) and more recently against viruses (Wilgenburg et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation